Citizen Science and Maine’s Fishermen: An Enlightened Approach to the Search for Ecological Solutions: The Margaret Chase Smith Essay - Ames, Ted (Maine Policy Review, 2017)
Ted Ames shares his view on the efforts of Maine’s commercial fishermen to engage in citizen science initiatives.